ANALISIS FAKTOR YANG MEMPENGARUHI MOTIVASI KADER POSYANDU BALITA DI KELURAHAN PURWOKERTO KIDUL - Arif Setyo Upoyo; Made Sumarwati (Kesmas Indonesia, 2008)
A few people want to be a Posyandu cadre. Be a cadre, time, energy, and money should be charitable. In Kecamatan Purwokerto Kidul, there are 10 Posyandu, which take care of 350 children under 5 years old. Each Posyandu has at least 4 health cadres which actively give attention to those children. This shows a very big community’s contribution. This study wants to explore what factors that contributes to cadre’s motivation. Descriptive analytic design was chosen. Thirty two cadres were collected through purposive sampling. Data were analyzed through chi square and logistic regression. Data analysis found that internal support (sig. 0.000), self esteem (sig. 0.002), external support (sig. 0.258), wage (sig. 0.440) and others appreciation (sig. 0.227). This can be concluded that internal motivation and self esteem was significantly motivated cadre to actively take care of the children. External support, wage and others appreciation played a little contribution in cadre’s motivation. Key words : level of motivation, Posyandu cadre *) lecturer Nursing Program FKIK Unsoed